2020
DOI: 10.1111/jace.17036
|View full text |Cite
|
Sign up to set email alerts
|

Searching for correlations between vibrational spectral features and structural parameters of silicate glass network

Abstract: Infrared (IR) and Raman spectroscopic features of silicate glasses are often interpreted based on the analogy with those of smaller molecules, molecular clusters, or crystalline counterparts; this study tests the accuracy and validity of these widely cited peak assignment schemes by comparing vibrational spectral features with bond parameters of the glass network created by molecular dynamics (MD) simulations. A series of sodium silicate glasses with compositions of [Na2O]x[Al2O3]2[SiO2]98−x with x = 7, 12, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 91 publications
2
62
0
Order By: Relevance
“…The decrease in υ Si‐O intensity is due to the reduction in the Si‐O bonds and the refractive index change as Al concentration increases 86 . Shifts towards lower wave numbers indicate longer Si‐O bond length distributions 87‐89 likely due to increases in Si‐O‐Al and/or NBOs associated with Si. The peak maximum of ISG‐A00N is shifted further toward the higher wave numbers of ISG‐C compared to ISG‐A00 by ~30 cm −1 which is likely caused by immiscible phase separation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in υ Si‐O intensity is due to the reduction in the Si‐O bonds and the refractive index change as Al concentration increases 86 . Shifts towards lower wave numbers indicate longer Si‐O bond length distributions 87‐89 likely due to increases in Si‐O‐Al and/or NBOs associated with Si. The peak maximum of ISG‐A00N is shifted further toward the higher wave numbers of ISG‐C compared to ISG‐A00 by ~30 cm −1 which is likely caused by immiscible phase separation.…”
Section: Resultsmentioning
confidence: 99%
“…further toward the higher wave numbers of ISG-C compared to ISG-A00 by ~30 cm −1 which is likely caused by immiscible phase separation. Based on the blue shift of the υ Si-O peak, the separated phase is expected to have shorter Si-O bond length distributions, [87][88][89] that is, closer to a silica-like structure.…”
Section: T G Analysis and High-temperature Oxide Melt Solution Calomentioning
confidence: 99%
“…33,34,45,46 We have shown that the main Si-O-Si stretch peak at ~1060 cm −1 can be related to the Si-O bond length distribution of the network in the case of silica and sodium silicate glasses. 14,47 Since the boron and aluminum contents are quite low here (see Table 1), we assume that the same could be applied to the glass series tested in this study qualitatively. Then, changes in the Si-O-Si stretch band, especially peak position and shape, could mean alteration of the glass structure in the corroded layer likely due to network re-arrangement or re-polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 For high durability glasses, the characterization of the corrosion behavior is challenging due to the low concentrations of ions being released into solution. 13,14 Despite the recent progress in pharmaceutical glass packaging, further improvement of the properties of the glass is demanded to meet the requirements related to mechanical strength and chemical durability. 15 To improve the chemical durability and mechanical properties of pharmaceutical glasses, a chemical strengthening treatment has often been applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation